Restorative Forest - Maulan, Suhardi; Mohd Taram, Emran @Zahrin; Mohd Yunus, Mohd Yazid; Ling, Koh Chee (Universiti Putra Malaysia, 2011)
The waterfall design in Sungai Gabai, Hulu Langat, Selangor, attempts to transform the conventional river recreation images to a competitive, attractive and restorative environment. The site’s environmental potential and their embedded forest-health restorative values are assessed. Environmental sensitivity, carrying capacity and selective deep green forest friendly-activities are adopted as the foundation of the design proposal. The existing natural visual quality is preserved and utilizes it for visitors’ attractions. The proposal includes a development of a foresthealth restoration activity centre that enables people to seek alternative solution in healing their psychological and physical fatigue.